Green purchase intention factors: A systematic review and research agenda - Orfa Nidia Patiño-Toro; Alejandro Valencia-Arias; Lucia Palacios-Moya; Hernán Uribe-Bedoya; Jackeline Valencia; Wilmer Londoño; Ada Gallegos (Sustainable Environment)
The intention to purchase green products is essential to promote sustainability and contribute to a healthier and environmentally conscious future. However, based on the research gaps, the objective is to explore the current study trends in relation to the research object. The proposed methodology involves a systematic review of the literature to assess the theories and variables that determine green purchase intention. The review will follow the parameters of PRISMA 2020 and will be conducted using the Scopus and Web of Science databases. The data were analyzed with Microsoft Excel® and VOSviewer software. Among the main results, it was found that green purchase intention is a growing topic in the scientific literature, with exponential growth in countries such as Germany, Italy, Malaysia, China, India, Taiwan, and the United States. Motivations include environmental concern, health, social awareness, and subjective norms. Psychobehavioral theories such as Theory of Planned Behavior (TPB) and Theory of Reasoned Action (TRA) have been validated in different contexts, emphasizing variables such as attitude, subjective norms, and perceived behavioral control. Although there are research gaps, there is an urgent need to address the comparison of factors between developed and developing countries. Future research should focus on emerging issues to promote environmental behavior and sustainable development.